Профессия PR-советника: требования, условия и функции (методические вопросы) - Некрасова, О. (Социология: теория, методы, маркетинг, 2005)
The author discusses the essence of a number of methodical issues related to require ments, conditions, and content of the functions performed by professional public relations counsel. Namely, special attention is paid to the following: the nature of public relations counsel, basing on which he/she works with any organization; pay ment arrangements; advance preparations; client education to develop full under standing of the scope and PR functions; working pattern and procedure of relations with the client; issues of confidentiality; client attraction and ethical methods of selling the PR-counsel profession.